Information Bulletin of the Central Committee of the Hungarian Socialist Workers' Party
German ed.: Informationsbulletin des Zentralkomitees der Ungarischen Soziallistischen Arbeiterpartei (ZK 31491). - French ed.: Bulletin d'Information du Comité central du Parti Socialiste Ouvrier Hongrois (ZK 30456). - Russian ed.: Informacionnyj bjulleten; Central'nogo Komiteta Vengerskoj Socialističeskoj Rabočej Partii (ZK 30309).